Macbeth : the 30-Minute Shakespeare. - Newlin, Nick (30-Minute Shakespeare Ser., 2010)
Planning a school or amateur Shakespeare production? The best way to experience the plays is to perform them, but getting started can be a challenge: The complete plays are too long and complex, while scene selections or simplified language are too limited. "The 30-Minute Shakespeare" is a new series of abridgements that tell the "story" of each play from start to finish while keeping the beauty of Shakespeare's language intact. Specific stage directions and character suggestions give even inexperienced actors the tools to perform Shakespeare with confidence, understanding, and fun!